De Ritis (AST/ALT) ratio as a predictor of early adverse outcomes following transcatheter aortic valve replacement - Haitham Abu Khadija; Jebrin Alkrinawi; Ali Abdullah; Omar Ayyad; Ammar Barakat; Salma Najjar; Alexander Kogan; Leonid Sternik; Alaa Shehady; Mohammad Masu’d; Duha Najajra; Mohammad Alnees (PLoS ONE, 2026)
Background Simple biochemical markers that capture systemic stress could refine short-term risk stratification after TAVR. We evaluated whether an elevated AST/ALT ratio predicts early adverse outcomes following transfemoral TAVR. Methods We retrospectively analyzed 733 consecutive patients undergoing transfemoral TAVR. The exposure was the preprocedural AST/ALT ratio categorized as low (<1.4; n = 478) or high (≥1.4; n = 255). Baseline characteristics were compared using t/Wilcoxon tests and χ²/Fisher’s exact tests. Thirty-day endpoints included all-cause mortality, acute kidney injury (AKI), stroke, and new-onset atrial fibrillation (NOAF). Kaplan–Meier failure curves were compared by the log-rank test. Cox models estimated hazard ratios (HRs) with 95% CIs; candidate covariates were prespecified and further refined with LASSO (10-fold cross-validation). Model assumptions were checked with Schoenfeld residuals. Results High AST/ALT was associated with greater 30-day risk of AKI (adjusted HR 3.18, 95% CI 1.80–5.63), stroke (adjusted HR 2.73, 95% CI 1.31–5.69), and NOAF (adjusted HR 2.35, 95% CI 1.57–3.51). For mortality, the crude association was not statistically significant (HR 2.07, 95% CI 0.91–4.68; p = 0.082) and remained non-significant after adjustment (HR 1.74, 95% CI 0.75–4.04; p = 0.197). Additional adjusted associations included higher AKI risk with high-intensity statins (HR 3.51, 95% CI 1.75–7.06) and baseline complete right bundle-branch block (HR 3.77, 95% CI 1.49–9.57). Conclusions An elevated preprocedural AST/ALT ratio independently identifies TAVR recipients at increased 30-day risk of AKI, stroke, and NOAF, but not mortality. Incorporating this inexpensive marker into routine assessment may help tailor periprocedural strategies and early surveillance after TAVR.